The Attitude of Kindergarten Teachers Toward Implementing Active Learning Strategies within the Interactive Unit Curriculum - سلمان لبنى ليث (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The philosophy of active learning is regarded as one of the fundamental strategies that must be adopted in the current era. It marks a shift from traditional methods based on memorization and rote learning to an approach where the learner becomes the focal point of the educational process. Accordingly, the present research aims to explore the attitudes of kindergarten teachers toward active learning strategies within the Interactive Experience Unit curriculum, and to examine the influence of academic specialization and years of service on these attitudes. The descriptive-analytical method was employed to collect data from a sample of kindergarten teachers. The objectives of the research were to: Identify the attitudes of kindergarten teachers toward the application of active learning. Examine the implementation of active learning in relation to the variables of academic qualification and years of service. To achieve these aims, the researcher developed an active learning scale grounded in relevant theoretical frameworks and previous studies. A questionnaire was administered to a sample of 100 teachers from the Al-Karkh Second Directorate. The instrument was designed to assess the degree of acceptance and practical application of active learning principles in classroom settings. After validating the scale through psychometric procedures—including item discrimination, content validity, and reliability analysis using Cronbach’s alpha—the findings revealed that teachers hold positive attitudes toward active learning. They highlighted its significance in fostering children’s thinking skills, boosting motivation, and enhancing classroom interaction. Furthermore, the results indicated no statistically significant differences in teachers’ attitudes based on either academic specialization or years of teaching experience. This suggests that the preference for active learning reflects a shared pedagogical conviction among teachers, independent of their field or length of service. The study concluded with a set of recommendations and proposals for further development in this area.